A Scientific Update on Juglans Regia Linn. - Verma, Gunjan; Sharma, Vandana (Asian Journal of Pharmaceutical Research and Development, 2020)
Medicinal herbs having a great role in human health care and welfare services. These herbs widely used in Ayurveda, Homeopathic and Allopathic system having various therapeutic properties. Walnut (Juglans regia L.) are the plants belonging to the family Juglandaceae commonly known as Akhrot. It is widely distributed in China, United State, Jammu & Kashmir, Himachal Pradesh, Arunachal Pradesh, Uttarakhand. It has different varieties such as Black walnut, English/Persian walnut, butternut/white walnut. J.regia L. have many marketed formulations such as Topical formulations like Walnut oil, Face wash, Exfoliating scrub, Soap, Shampoo, Hair color and Oral formulations like capsules, tinctures, dilutions, shell powder. Chemical study reveals that J.regia L. contains Juglone, Alkaloids, Flavonoids, Saponins, Polyphenols, Polyunsaturated fatty acids, Oleic acids, Linoleic acids, Proteins, Napthaquinones, Ascorbic acid, Sitosterol, Tannins. Walnut contains different nutritional components like Carbohydrates, Proteins, Dietary fibres, Iron, Phosphorus, vitamin E & C. This plant possess beneficial effects include Antimicrobial, Antioxidant, Anticancer, Antidiabetic, Anthelmintic, Antiinflammatory, Antidepressant, Hepatoprotective, Antiulcer, Antiageing and Hypocholestermic activity and other therapeutic activities. It is believed to be used in Dental plaque, Gingivitis, Oral hygiene, Eczema, Hemorrhoids, Burns, Blood Purifier, Dyeing or Colorant, Antiseptic and Astringent. In the present study, Pharmacognostic and Pharmacological properties of J.regia L. have been discussed. This review highlights the various Ethanobotanical and traditional uses as well as Pharmacognostic and Pharmacological report on J.regia L.